2023
DOI: 10.1186/s12951-023-01788-4
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes derived from human adipose mesenchymal stem cells ameliorate hepatic fibrosis by inhibiting PI3K/Akt/mTOR pathway and remodeling choline metabolism

Abstract: Liver fibrosis is a chronic liver disease with the presence of progressive wound healing response caused by liver injury. Currently, there are no approved therapies for liver fibrosis. Exosomes derived from human adipose mesenchymal stem cells (hADMSCs-Exo) have displayed a prominent therapeutic effect on liver diseases. However, few studies have evaluated therapeutic effect of hADMSCs-Exo in liver fibrosis and cirrhosis, and its precise mechanisms of action remain unclear. Herein, we investigated anti-fibroti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 65 publications
1
17
0
Order By: Relevance
“…40 Additionally, hADMSC-EXOs attenuated HSC activation and inhibited the progression of liver fibrosis by inhibiting the PI3K/AKT/mTOR signaling pathway and regulating choline metabolism. 19 AD-MSC-derived exosomes have also been demonstrated to promote the anti-tumour response of NKT cells in rats, resulting in HCC suppression, an increased early apparent diffusion coefficient (ADC), and low-grade tumour differentiation. 41 However, MSC-EVs can also contribute to cancer progression.…”
Section: Native Evs In Liver Diseases Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…40 Additionally, hADMSC-EXOs attenuated HSC activation and inhibited the progression of liver fibrosis by inhibiting the PI3K/AKT/mTOR signaling pathway and regulating choline metabolism. 19 AD-MSC-derived exosomes have also been demonstrated to promote the anti-tumour response of NKT cells in rats, resulting in HCC suppression, an increased early apparent diffusion coefficient (ADC), and low-grade tumour differentiation. 41 However, MSC-EVs can also contribute to cancer progression.…”
Section: Native Evs In Liver Diseases Therapymentioning
confidence: 99%
“…[15][16][17] Furthermore, intravenously injected EVs tend to accumulate in the liver. 18,19 In addition, with the rise of RNA therapy, EVs, as endogenous biological carriers, can protect nucleic acid molecules from being broken down and deliver drugs to the lesion site. Moreover, engineered EVs have recently emerged as a new therapeutic strategy and are promising as an alternative approach to EV-based therapy (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Among other examples of phenotypic changes induced, exosomes were shown to contribute to the polarization of macrophages [ 115 ]. Exosomes have also been described as players in epithelial–mesenchymal transition (EMT) in a variety of pathological conditions, including fibrosis and cancer [ 116 , 117 ]. However, the miRNA content of exosomes, depending on the emitting cells, would mediate potentially antagonistic effects on EMT, revealing both the promotion and inhibition roles [ 118 , 119 ].…”
Section: Exosomes Are Small Specialized Extracellular Vesicles (Evs)mentioning
confidence: 99%
“…This would be promising in treating liver fibrosis, liver injury, cirrhosis, liver failure, and liver cancer. Two recent studies have shown that MSCs could hinder liver fibrosis progression in mice by inhibiting the activation of hepatic stellate cells [20, 21]. Meanwhile, splenic vein injection of MSCs contributed to the attenuation of acute liver injury in dogs [22].…”
Section: Mesenchymal Stromal Cellsmentioning
confidence: 99%